Clinical Outcome Evaluation of an Antimicrobial Stewardship Program in an Accountable Care Organization. (4th October 2017) - Baumgartner, Meredith; Giddens, Julie; Asche, Carl; Ren, Jinma; Walayat, Saqib; Asghar, Muhammad; Cotter, John
Abstract: Background: On a national level it is known that the daily misuse of antibiotics leads to delayed recovery, increased hospital length of stay, recurrent infection and even death. At the organization-level, antimicrobial stewardship programs have been developed to tackle these issues. As these programs develop, research is greatly needed to assess the associated clinical outcomes. This study was conducted to compare such clinical outcomes as length of stay (LOS), 30 day readmission and mortality pre and post implementation of a formal antimicrobial stewardship program. Methods: Retrospective review of randomized adult patients at a large community teaching facility receiving meropenem, linezolid, daptomycin, tigecycline, micafungin, vancomycin, piperacillin/tazobactam, levofloxacin, between April 2010 to March 2011 (Pre Intervention: n = 228) and April 2012 to March 2013 (Post Intervention: n = 219). The assessment of clinical outcomes was achieved using logistic regression for 30 day readmission and status of deceased on discharge, and a generalized linear model with gamma distribution for ICU LOS and inpatient LOS. Results: The Pre Intervention group had a 30 day readmission rate of 16.7% (38/228), a Status on Discharge of Deceased of 10.5% (24/228), an ICU LOS of 13.4% (14/228), and an Inpatient LOS of 11.6% (10.5/228). In contrast, the Post intervention group had a 30 day readmission rate of 7.3% (16/219; P = 0.001), a Status on Discharge of Deceased of 3.7% (8/219; P = 0.002), an ICU LOS of 9% (7.9/219; P = 0.01), and an Inpatient LOS of 8.8% (7.6/219; P = 0.018). Conclusion: The multidisciplinary efforts of the program were associated with statistical significant decreases in 30 day readmission rates, mortality on discharge and ICU and inpatient LOS. These results assist in validating the true clinical outcome benefits of antimicrobial stewardship programs. Disclosures: All authors: No reported disclosures.